Pitong Sulyap sa Pilosopiya ng Wika ni Padre Ferriols - Strebel, Wilhelm Patrick Joseph S (Archīum Ateneo, 2018)
The Jesuit priest, Roque J. Ferriols is well known in Ateneo de Manila University as the first philosophy professor to teach philosophy in Filipino. Since 1969 until he retired in 2014, he taught all of his philosophy classes, both in the undergraduate and graduate levels, in Filipino. His example was followed by many Ateneo philosophy faculty. Since around the 1990s the number of philosophy classes taught in English and in Filipino had a 50/50 percentage ratio. This ratio continued on to the present time. As the tradition of teaching philosophy in Filipino nears its 50th anniversary in 2019, Ferriols continues to be appreciated as the trailblazer of the tradition. Even if Ferriols never taught philosophy of language, his teaching pedagogy and his writings reflect important insights relevant to the philosophy of language. This paper seeks to draw these insights from three different texts written years apart from each other but all within Ferriols’s teaching career. The texts are A Memoir of Six Years, an essay written for Philippine Studies in April 1975; Sinauna Bilang Potensyal, the final chapter of his Pambungad sa Metapisika published in 1991; and a few sections of his memoirs, Sulyap sa Aking Pinanggalingan published in 2016. In so doing, this paper seeks to spearhead critical discussions of Ferriols’s philosophy of language stressing on how these insights come from the context of pedagogy and as such how these insights reflect the context, experience, lifeworld and historicity of the learner towards a deeper understanding of the human being qua linguistic being and human being qua human being. Thus, the paper seeks to show that the conscious and deliberate awareness of language and culture often seen in the celebration of Buwan ng Wika distracts us from the reality and nature of language and culture, and obscures the role of language and culture in human life. The main emphasis of this paper is the insight that the reality, nature, and role of language and culture could be found in the actual lived experience of the world as linguistic reality. In other words, we do not experience the world “through the medium” of language and culture. What really happens is that our experience of the world is language and culture. This paper does not pretend to be exhaustive in that it cannot fully follow the logical and phenomenological implications of the insights it brings to the reader’s attention. Its task is to make thematic these insights and note that these insights are conscious to Ferriols as a philosophy teacher so that these themes and insights could be further mulled over and reflected upon by other writers and scholars seeking to elucidate on the subject matter.